PERSONAL PRONOUN ERRORS IN TRANSLATING SIMPLE SENTENCES FROM BAHASA INDONESIA TO ENGLISH - Fenti Pratama Sari; Ira Maisarah (PARADIGM: Journal of Language and Literary Studies, 2022)
The ultimate objectives of this research were to find out the kinds of English personal pronouns errors in translating simple sentences from Bahasa Indonesia to English and the most dominant errors made by the students in the tenth grade of SMKS Agro Maritim Muhammadiyah Bengkulu in using a personal pronoun. This study employs the descriptive-qualitative method. This research has conducted the students in the tenth grade of SMKS Agro Maritim Muhammadiyah Bengkulu in the academic year of 2021/2022, consisting of 13 students. The first result of this research displays that the students made errors in using four types of personal pronouns. They are personal pronouns as possessive adjectives, personal pronouns as an object, personal pronouns as subject, and personal pronouns as possessive pronouns. The second result showed that the most dominant error made by the students in using personal pronouns is possessive adjectives. The findings indicate that the students in the tenth grade of SMKS Agro Maritim Muhammadiyah Bengkulu face the problem of the personal pronoun.